The Role of Internal Audit in Enhancing Risk Awareness at PT X - Laxmi Jullianeth; Fitriany Fitriany (Eduvest - Journal of Universal Studies, 2024)
Internal audit is a function designed to assist companies in achieving their strategic goals. Internal audit is considered only as a fault finder so that its function is less acceptable in work unit. Over time, internal audit has been accepted as a compliance tester in an organization. This compliance testing results in activities that are still a formality without any real action from the implementation of compliance procedures. In accordance with the times, especially in the field of technology, various kinds of risks threaten each organization such as cyber, market and other risks that affect achievement of organizational goals. Risk-based audits are starting to be launched and implemented to be able to help management see which side of each work unit has potential risks and actions to mitigate risks. Internal audit designs each audit plan in each work unit to be able to sort out the work unit in each potential risk in each work unit. Internal audit findings are grouped into three parts of the risk group, namely, low, medium and high to be able to provide recommendations for urgent action with a high level of risk. Awareness of each work unit is expected to be increased from the audit results so that in the future each work unit conducts self-assessment and supervision of any risks that arise or have potential to arise in its work unit, and reports to Management so that the necessary follow-up can be carried out to prevent risks that will occur to a minimum.